Mitochondrial developmental encephalopathy with bilateral optic neuropathy related to homozygous variants in IMMT gene - Marco‐Hernández, Ana Victoria; Tomás‐Vila, Miguel; Montoya‐Filardi, Alejandro; Barranco‐González, Honorio; Vilchez Padilla, Juan Jesus; Azorín, Inmaculada; Smeyers Dura, Patricia; Monfort‐Membrado, Sandra; Pitarch‐Castellano, Inmaculada; Martínez‐Castellano, Francisco (Clinical genetics, 2022)
IMMT gene codes for mitofilin, a mitochondrial inner membrane protein that regulates the morphology of mitochondrial cristae. The phenotype associated with mutations in this gene has not been yet established, but functional studies carried out show that its loss causes a mitochondrial alteration, both in the morphology of the mitochondrial crests and in their function. We present two cousins from an extended highly consanguineous family with developmental encephalopathy, hypotonia, nystagmus due to optic neuropathy. The likely pathogenic homozygous c.895A>G (p.Lys299Glu) variant in the IMMT gene co‐segregates with the disease and associates altered mitochondrial cristae observed by electron microscopy.